1999
DOI: 10.1104/pp.119.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Two Arabidopsis Mutants That Overproduce Ethylene Are Affected in the Posttranscriptional Regulation of 1-Aminocyclopropane-1-Carboxylic Acid Synthase1

Abstract: The Arabidopsis mutants eto1 (ethylene overproducer) and eto3 produce elevated levels of ethylene as etiolated seedlings. Ethylene production in these seedlings peaks at 60 to 96 h, and then declines back to almost wild-type levels. Ethylene overproduction in eto1 and eto3 is limited mainly to etiolated seedlings; light-grown seedlings and various adult tissues produce close to wild-type amounts of ethylene. Several compounds that induce ethylene biosynthesis in wild-type, etiolated seedlings through distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 54 publications
9
138
0
2
Order By: Relevance
“…The eto2 mutation does not increase the steady state level of ACS5 mRNA, which suggests that the mutation acts post-transcriptionally (Vogel et al, 1998). Furthermore, in both eto1 and eto3 , the steady state levels of all of the ACS transcripts examined were not significantly higher than those observed in wild-type seedlings, although the level of ACS activity from eto1 and eto3 etiolated seedlings was highly increased (Woeste et al, 1999). These results suggest that these mutants also are affected in the posttranscriptional regulation of ACS.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The eto2 mutation does not increase the steady state level of ACS5 mRNA, which suggests that the mutation acts post-transcriptionally (Vogel et al, 1998). Furthermore, in both eto1 and eto3 , the steady state levels of all of the ACS transcripts examined were not significantly higher than those observed in wild-type seedlings, although the level of ACS activity from eto1 and eto3 etiolated seedlings was highly increased (Woeste et al, 1999). These results suggest that these mutants also are affected in the posttranscriptional regulation of ACS.…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies of the ethylene-overproducing mutants eto1 and eto3 suggested that these mutations affect the post-transcriptional regulation of ACS (Woeste et al, 1999). To learn more about the mechanism by which ACS is regulated at the post-transcriptional level, the ETO3 gene was cloned using a map-based approach.…”
Section: The Eto3 Mutation Results From a Single Amino Acid Change Inmentioning
confidence: 99%
“…Intriguingly, CUL3 can be RUB modified (Figueroa et al, 2005) and is a component of a ubiquitin-protein ligase that can include ETO1, which targets ACS5 for ubiquitin-dependent degradation (Wang et al, 2004). ACS enzyme activity (Woeste et al, 1999) and ACS5 protein levels (Wang et al, 2004) are enhanced in eto1 mutants, and it will be interesting to learn whether ACS5 is similarly stabilized in ecr1, rce1, or rub mutants. It remains mysterious why axr1 displays opposite ethylene phenotypes, ethylene resistance (Timpte et al, 1995) and less ethylene production than wild type (Bostick et al, 2004), compared to other RUB pathway mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene biosynthesis is reported to be downregulated through 1-aminocyclopropane-1-carboxylate malonylation (Guo et al, 1993). This pathway does not seem to interfere with embryo development, since ethylene overproducer mutants exhibit normal embryo development (Woeste et al, 1999). Waxes that contain VLCFA are deposited once embryo morphogenesis is achieved and therefore are unlikely to be involved.…”
Section: Accase 1 Is Necessary For Embryo Developmentmentioning
confidence: 99%